Komunikasi Pemasaran Dengan Strategi Promosi Bioskop CGV Central Park Untuk Menarik Minat Penonton - Iswahyu Pranawukir; Misnan Misnan; Alamsyah Alamsyah (Universitas Bina Sarana Informatika, 2022)
The activities of marketing communication through promotional strategies are a significant efforts for CGV Central Park Cinemas in order to increase the interests of their customers.The purpose of this study is to determine the marketing communication strategy of CGV Central Park by looking at their mixtures of promotional efforts as well as all the challenges within their promotional activities. Furthermore, the research is also intended to search for the most prominent form of the CGV Cinema Central Park promotion efforts.The research applies descriptive qualitative methods. Data collection is carried out through observations, interviews, literature reviews as well as documentation. The key informants are determined by using the purposive sampling. analysis of data is carried out through data reduction, data presentation and conclusion.This research shows that the CGV Cinema Central Park has been actively promoted itself digitally through social media platforms of Gopay and Linkaja. This approach is used as a co-branding strategy so that the hard selling approach can still be used to boost the ticket sales in terms of price (discounts, presale, cashback through sales promotion program, personal sales and those direct marketing (direct marketing).Compared to advertising promotions, it seems that they are quite responsive in order to implement thr soft selling through sharing advertisements to the mall tenants, advertisement that placed in eye-catching spots, Central Park mall customers, as well as at interactive media and marketing Public relations. In addition, they are also actively promoting themselves to companies by offering mixture of programs such as Culturflex (Nobar, gathering, dance cover, shooting, shooting venue). It seems that there are still some obstacles for using CGV Central Park social media due to the limitation applied in sharing the content on IG (Instagram). This is indeed a part of policy coming from the central CGV. Clearly, this particular aspect is an inhibiting factor that limit them to work more creative and innovate in order to attract more interests among their customers .